Optimal Sewer Network Design Including Pumping Stations - Juan Saldarriaga; Juana Herrán; María A. González; Yesid Coy; Pedro L. Iglesias-Rey (Engineering proceedings, 2024)
In urban areas with a flat terrain, pumping stations must be included to elevate wastewater and avoid extreme excavation depths. These systems are characterized by high operational costs due to the pump’s power consumption. The present work presents a methodology for the optimal design of sewer networks including pumping stations, whose objective function is to minimize the construction and operation costs of the system. The methodology was tested on three sewer benchmark networks using two cost functions proposed in the literature. In all the sewer benchmarks, the cost achieved in the present work was compared with the best costs reported in the literature.